Effect of foliar applications of phosphite on post-harvest potato tubers - Lobato, M.C. (2011)
The utilization of phosphites (Phi) could be considered as another strategy to be included in integrated disease management programmes to reduce the intensive use of fungicides and production costs. The aim of the present work was to analyze whether the beneficial effects of phosphite treatment previously observed in potato plants grown under greenhouse conditions, were reflected after harvest of field grown potatoes, both in disease protection and in yield. In addition, biochemical compounds possibly involved in induced defence responses by Phi, like phytoalexins, pathogenesis related proteins and oxidative stress enzymes were measured. Foliar applications of KPhi to field grown crops resulted in post-harvest tubers with a reduced susceptibility to Phytophthora infestans, Fusarium solani and Erwinia carotovora infections, suggesting that this compound induced a systemic defence response. An increase in phytoalexin content in P. infestans inoculated tubers obtained from Phi-treated plants suggests their participation in the defence response. Chitinase content increased 72h after wounding or inoculation with P. infestans in tubers from KPhi-treated plants compared to wounded or infected tubers from non-treated plants. Contrary to this, the isoforms of β-1,3-glucanases analyzed did not increase in the tubers of Phi-treated plants. The increment in peroxidase and polyphenol oxidase activities indicated that these enzymes could be part of the Phi defence mechanism. No negative effects were observed in potato yield at harvest, measured as total tuber weight and dry matter, after foliar KPhi treatment. This suggests that the energetic cost involved in the defence response activation would not be detrimental to plant growth.